HUBUNGAN BILATERAL KUBA-AMERIKA SERIKAT TERKAIT PEMBANGUNAN PELABUHAN MARIEL DAN ZONA PERDAGANGAN BEBAS - Bayu Tri Anggoro (ISIP UMY 264, 2015)
The special period that Cuba experienced post-Soviet brought Cuba to the changes in terms of relations with neighboring countries such as Venezuela and Brazil. Relations with these two countries enough for Cuba to survive in economic and political terms. The problem is that US embargo that has yet to recover fully. Embargo excluded for food and medicine. The ideological differences make it difficult to Cuba and US cooperate. With the idea of pragmatism, Cuba and US priority to trade relations. The US will be willing to lift its embargo in the near future. The desire will be supported by the US society. With the lifting of the embargo, trade cooperation will be done safely. Cuba will begin the new life with prosperity.